Motivasi Belajar Pada Remaja yang Tinggal di Panti Asuhan - Sandri, Ritna (Psikoislamika: Jurnal Psikologi Islam, 2015)
The research subjects were students grade 3 junior and the children who live in orphanages, they are teenagers who are experiencing a decline in motivation to learn. The Study aims to increase the motivation to learn by applying group counseling. Data collection techniques are observation and interviews. Intervention consists of four phases: the firSt or early Stage, phase II or phase transitions, Stage III or Stage cohesion and productivity and Stage IV or Stage of consolidation and termination which is the laSt Stage in the counseling group. After the intervention, the subject of understanding and solving the problems they are facing, with the completion of the problems they are facing, the high motivation to learn them back.